The use of lichens in post-smelting dumps reclamation – preliminary results of experimental cultivation of selected species on slag substrate - Rola Kaja; Osyczka Piotr (E3S Web of Conferences, 2017)
Conventional reclamation interventions of post-smelting slag dumps being undertaken so far either failed or produced poor results. Certain lichens, especially of the genus Cladonia, are known as effective colonisers of bare ground in anthropogenic habitats. The paper presents preliminary results of the experiment aimed at the evaluation of lichen usefulness in reclamation interventions. The cultivation in vivo involving transplantation of lichens directly on slag substrate was established in 2015. Five species, i.e. Cladonia rei, C. cariosa, C. pyxidata, C. subulata, C. macilenta, were transplanted into 32 cuvettes filled with sterilised slag substrate. The sample weight of 2 and 6 g were used and half of cuvettes were regularly supplied with 2% malt solution. The first important symptoms at the present stage of the experiment are as follow: the growth of thalli has appeared only in the case of first three species; C. rei shows the most effective development; cuvettes with 6 g sample weight are characterized by higher coverage of fresh lichen thalli; lichen biomass are visually higher in cuvettes treated with malt solution. The results give us reason to believe that lichens could be successfully used as an alternative element during planning of slag dumps reclamation in the future.